A Survey Of Spectrum Sharing Techniques In 5g Communication Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a days, spectrum has become under the basic commodities of life due to communication and data usage. For any type of communication, spectrum is an important factor to create a channel to pass the information. It becomes a scare resource due to increasing demand and new technology development. In order to satisfy the demands and incorporate the new technology, spectrum sharing concept is used. Spectrum sharing gives an advantage of increasing the spectrum efficiency  and revenue for the licensed spectrum holders. In this paper, spectrum sharing in 5G communication network is discussed by analysing various techniques. The basic approach of spectrum sharing is based on improving the sensing of the channel  for transmission. Sensing schemes can  be  classified as random sensing, compressed sensing, channel assignment schemes like greedy channel assignment etc., The techniques for spectrum sharing is broadly classified into four types namely Graph based access, auction based access, game theory based access and carrier aggregation based access. Mostly, the spectrum sharing scheme is evaluated in terms of throughput, blocking probability and sensing time. In this, the throughput of the system is considered for comparing the different spectrum sharing approaches. Among theses, the virtual coalition formation game theory is best for the spectrum sharing in 5G network which can provide the throughput of 11.5 Gbps for 100 users.